ALTERNATIF KEBIJAKAN UNTUK FLY ASH AND BOTTOM ASH (STUDI KASUS: PP NO. 22 TAHUN 2021) - Ghefira Nurul Qolbi; Budhi Gunawan; Yogi Suprayogi Sugandi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The need for electricity supply in Indonesia is increasing amid the availability of main raw materials which can be considered "insufficient". Departing from this, the government plans to increase power generation capacity which is then outlined in the Electricity Supply Business Plan (RUPTL) since 2017. However, instead of using renewable energy, the power plant used is a power plant with coal as raw material. Even though the threat of climate change is increasingly real for the whole world. Indonesia's dependence on coal was increasingly felt when the Government issued PP No. 22 of 2021 concerning the Implementation of Environmental Protection and Management which is a derivative of Law no. 11 of 2020 concerning Job Creation. In this regulation, Fly Ash and Bottom Ash (FABA) dust, which is the result of burning coal, is removed from the Hazardous and Toxic Waste (B3). The purpose of this study is to provide alternative policies for policy makers by using descriptive qualitative methods in the review process. This study uses a qualitative method by utilizing secondary data with the results in the form of an explanation of alternative policies in overcoming the problem of coal policy which is summarized in PP no. 22 of 2021.